Quality management solution for physical education process for students - Tran Thu Hang, (IJRDO- Journal of Educational Research, 2020)
Physical education helps students form and develop physical ability and physical culture, a sense of responsibility for the health of themselves, their families and the community. At the same time, know how to choose a sport that suits their athletic ability to practice; know to adapt to living conditions, be optimistic and share with everyone;... One of the solutions to improve the quality of learning and training of students is to ensure the quality of the physical education process, in which, focusing on implementing well the solutions: Managing the teaching process of lecturers; Managing the learning and physical training processes of students; Managing physical education support activities of students; Managing the coordination of units and individuals in implementing the physical education task.